Csk controls leukocyte extravasation via local regulation of Src family kinases and cortactin signaling - Stegmeyer, Rebekka I.; Holstein, Katrin; Spring, Kathleen; Timmerman, Ilse; Xia, Min; Stasch, Malte; Möller, Tanja; Nottebaum, Astrid F.; Vestweber, Dietmar (Frontiers in Immunology, 2024)
C-terminal Src kinase (Csk) targets Src family kinases (SFKs) and thereby inacNvates them. We have shown previously that Csk binds to phosphorylated tyrosine 685 of VE-cadherin, an adhesion molecule of major importance for the regulaNon of endothelial juncNons. This tyrosine residue is an SFK target and its mutaNon (VE-cadherin-Y685F) inhibits the inducNon of vascular permeability in various inflammaNon models. Yet, surprisingly, it increases leukocyte extravasaNon. Here we have invesNgated whether endothelial Csk is involved in these effects. We found that absence of Csk in endothelial cells augmented SFK acNvaNon and the phosphorylaNon of VE-cadherin-Y685, but had no net effect on vascular leak formaNon. In contrast, lack of endothelial Csk enhanced leukocyte adhesion and transmigraNon in vitro and in vivo. Furthermore, silencing of Csk increased tyrosine phosphorylaNon of the SFK-substrate cortacNn. Importantly, the effects of Csk silencing on the increase of SFK-acNvaNon, cortacNn phosphorylaNon and neutrophil diapedesis were all dependent on Y685 of VE-cadherin. DeleNon of cortacNn, in turn, erased the supporNng effect of Csk silencing on leukocyte transmigraNon. We have previously shown that leukocyte transmigraNon is regulated by endothelial CortacNn in an ICAM-1 dependent manner. In line with this, blocking of ICAM-1 erased the supporNng effect of Csk silencing on leukocyte transmigraNon. CollecNvely, our results establish a negaNve feed-back loop that depends on the phosphorylaNon of VE-cadherin-Y685, which recruits Csk which in turn dampens the acNvaNon of SFK and cortacNn and thereby clustering of ICAM-1 and the extravasaNon of neutrophils.